Oestrogen Induced Ovarian Hyperplasia Leading to Cancer in the Rat Ovary - Govind Pandey, Dr (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe present study was aimed to assess the carcinogenic effect of a highly potent semisynthetic oestrogen, ethinyl oestradiol (EO) on the rat ovary. The EO was administered to different groups of rats @ 250, 500 and 750 Î¼g/kg body weight, orally, weekly for 16 and 20 weeks. On the 17th week, the ovarian tissues revealed marked congestion and fibrosis. Degeneration and necrosis of follicular tissues were also noticed. On the 21st week, these changes were more marked. In general, extensive fibrosis, thickening of blood vessel walls, follicular tissue degeneration and necrosis were noticed. At this period, EO (750 Î¼g/kg) caused papillary proliferation in surface epithelium and hyperplasia of follicular cells, which indicated the development of cancer in the rat ovary. The extent and severity of ovarian damage were dose and time dependent, suggesting that the EO at higher dose for prolonged period (750 Î¼g/kg, orally, weekly for 20 weeks) may produce hyperplasia leading to cancer in the ovary.